1996
DOI: 10.1046/j.1537-2995.1996.36996420753.x
|View full text |Cite
|
Sign up to set email alerts
|

Sources and sequelae of bacterial contamination of hematopoietic stem cell components: implications for the safety of hematotherapy and graft engineering

Abstract: These studies suggest that, despite careful attention to sterile procedures, low-level contamination of hematopoietic stem cell components can be introduced before or during manipulation as well as at thawing, and that standards for monitoring of the procedures for collection, processing, cryopreservation, thawing, and transfusion of hematopoietic progenitor cells are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
1
7

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 31 publications
6
62
1
7
Order By: Relevance
“…Previous studies have reported microbial contamination rates within the same range, varying from 1.6 to 4.5%. 9,13,14 Most of the bacteria isolated in this series are part of normal skin flora, predominately CNS -detected in 32 products (87%). The data are consistent with other published studies that also show skin bacteria as the most common microbial contaminant.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies have reported microbial contamination rates within the same range, varying from 1.6 to 4.5%. 9,13,14 Most of the bacteria isolated in this series are part of normal skin flora, predominately CNS -detected in 32 products (87%). The data are consistent with other published studies that also show skin bacteria as the most common microbial contaminant.…”
Section: Discussionmentioning
confidence: 93%
“…All autologous transplant patients had neutrophil recovery at a median of 10 days (range, [8][9][10][11][12][13][14]. Among the allogeneic transplant patients, all but one engrafted in a median of 13 days (range, 5-21).…”
Section: (8%)mentioning
confidence: 99%
“…In these cases, the contamination may be, according to the source of stem cells, from 0 to 4.5% in peripheral blood to as high as 26% in bone marrow. [5][6][7][8][9][10] Peripheral blood progenitor cells (PBPCs) have been increasingly used for both autologous and allogeneic transplants. In autologous PBPC transplants (APBPCT), cells are obtained frequently by apheresis through a central venous line, but this is also known to be a possible route for infection.…”
Section: Introductionmentioning
confidence: 99%
“…J. Padley et al, 2003;D. Padley, Koontz, Trigg, Gingrich, & Strauss, 1996;Schwella et al, 1994;Webb et al, 1996). Along with this, bacteria, fungi and viruses are able to survive in the liquid nitrogen storage phase and crosscontaminations between different units, stored in the same container have been observed (Bielanski, 2005;Bielanski, Bergeron, Lau, & Devenish, 2003;Bielanski & Vajta, 2009 Kamble et al, 2005).…”
Section: Infectious Considerationsmentioning
confidence: 99%